Pengembangan Kurikulum Pendidikan dan Globalisasi, Dampak Globalisasi Terhadap Tradisi Pendidikan Islam - Sundari Sundari; Himya Sipitri; Hilmin Hilmin (CV. Alim's Publishing, 2024)
Globalization has driven profound changes in educational curricula. A more inclusive and globally oriented approach is becoming a major trend. The Islamic education curriculum is not immune from these changes. There are efforts to integrate Islamic educational materials with a broader understanding of the world and global culture. In some cases, Islamic education curricula adopt a more progressive approach with a focus on critical thinking skills, foreign languages, and digital literacy. Globalization has introduced various new learning approaches and methods. Traditional Islamic education, which often consists of rote memorization and reproduction of sacred texts, faces pressure to adopt an approach more oriented towards understanding social and global contexts. Globalization has opened access to international educational resources through technology. This allows Islamic students and teachers to access new information and knowledge more easily, which can change the way Islamic education is taught and studied.